Littoral age 0+ fish distribution in relation to multi-scale spatial heterogeneity of a deep-valley reservoir - Kratochvíl, Michal (Jihočeská univerzita, 2013)
The distribution of the littoral age 0+ fish assemblage was studied with respect to spatial heterogeneity of a deep-valley reservoir over the entire growing season. The abundance and diversity of age 0+ fish were also examined in different habitat types along the longitudinal profile of the reservoir during the daytime.
Littoral age 0+ fish distribution in relation to multi-scale spatial heterogeneity of a deep-valley reservoir
Keywords: Habitat preference; Electrofishing; Growing season; Slope steepness; Percids; Cyprinids; Habitat preference; Electrofishing; Growing season; Slope steepness; Percids; Cyprinids